2020
DOI: 10.3389/fimmu.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

S100A12 Expression Is Modulated During Monocyte Differentiation and Reflects Periodontitis Severity

Abstract: Lira-Junior et al. S100A12 in Periodontitis increased in inflamed tissue cultures, potentially as a result of enhanced production by monocyte-derived cells. This study implicates the involvement of S100A12 in periodontitis pathogenesis, as evidenced by increased S100A12 expression in inflamed gingival tissue, which may be due to altered circulatory monocytes in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…This Previous studies found that S100A12 has different functions including chemotactic activity, inflammatory reaction, oxidative stress, and activation of intracellular signaling cascades. Mounting evidence clarified that S100A12 is elevated and involved in several inflammatory diseases, such as inflammatory bowel disease, rheumatoid arthritis, juvenile idiopathic arthritis, cystic fibrosis, and periodontitis (18)(19)(20)(21). According to recently published studies, S100A12 has been implicated in the process of many pulmonary inflammatory diseases (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Previous studies found that S100A12 has different functions including chemotactic activity, inflammatory reaction, oxidative stress, and activation of intracellular signaling cascades. Mounting evidence clarified that S100A12 is elevated and involved in several inflammatory diseases, such as inflammatory bowel disease, rheumatoid arthritis, juvenile idiopathic arthritis, cystic fibrosis, and periodontitis (18)(19)(20)(21). According to recently published studies, S100A12 has been implicated in the process of many pulmonary inflammatory diseases (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have demonstrated that the counts of immune cells, such as B cells, T cells, and NK cells, were strongly correlated with the severity in CAP patients (15)(16)(17). Previous studies suggested that an increase of S100A12 is associated with several inflammatory diseases, such as inflammatory bowel disease, rheumatoid arthritis, juvenile idiopathic arthritis, cystic fibrosis, and periodontitis (18)(19)(20)(21). Moreover, recent researches indicated that S100A12 can be implicated in idiopathic pulmonary fibrosis, acute lung injury, pulmonary hypertension, interstitial lung disease, and acute respiratory distress syndrome (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generated immune oral gingival models by incorporating primary monocytes, peripheral blood mononuclear cells, or myeloid cancer cell lines (MonoMac-6 [MM6], U937, or THP-1 cells) and by observing changes in inflammatory markers and proteases in response to bacterial LPS, [18][19][20][21] bacterial biofilms, 22 or X-ray treatment. 23 While the use of myeloid cancer cell lines presents fewer technical limitations and reproducibility compared with primary immune cells, there is good evidence that their phenotype and function is markedly altered compared with primary cells, with the often used THP-1 cells shown to express aberrant levels of key macrophage phenotypic markers and thus respond differently to stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…9 The stimulation by other inflammatory mediators can change the protein conformation of S100A12, thereby exposing the binding site of target protein, which can interact with specific proteins or peptides to play biological functions. 10 These calciumbinding proteins control critical cellular pathways such as cytoskeleton, cell migration and adhesion, active oxidative defense, wound healing, activation of inflammatory cells, chemotaxis, and antimicrobial effects, which are also involved in the pathophysiological process of metabolic and neoplastic diseases. 11 So, we considered that S100A12 may regulate inflammation factors to prevent osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%